Ecotheology In Review of Theory 0f Deep Ecology Arne Naess - Naufal Kurniawan; Sindi Kania; Widya Indah Sari; Yeni Oktavia (International Journal of Education, Vocational and Social Science, 2023)
Religion and the environment are something different. The relationship between religion and the environment is called ecotheology. Ecotheology is literally defined as a combination of theology and ecology which emphasizes observation and theological reflection on temporary natural conditions as God's creation which is threatened with destruction due to human behavior. This ecotheology emphasizes that God is not solely on the side of humans but on all of His creation. This study aims to analyze the relationship between religion and the environment (ecotheology) which ultimately influences human behavior towards the environment. In this study, researchers used library research methods with a descriptive approach. Analysis of the research data presents Arne Naess' s Deep Ecology theory as an analytical knife to achieve resolution of the problem under study. The results of the research show that to understand environmental sustainability is not only enough to think about it but also requires awareness that can be realized in every activity. Through religion which is used as a driving force and self-motivation, humans can be controlled, especially in terms of behavior in managing and utilizing the environment